Disintegration of waste activated sludge with composite ferrate solution: Sludge reduction and settleability. (November 2018) - Zhang, Yanping; Hu, Ruiqi; Tian, Jiayu; Li, Tiantian
Graphical abstract: Highlights: Composite ferrate solution enhanced sludge disintegration and settleability. The Fe(VI), ClO − and OH − in CFS leaded to the better performance of CFS. The small-particle sludge, Fe 3+ and Ca 2+ promote the sludge settleability. Abstract: Sludge reduction has been a key issue in waste activated sludge (WAS) treatment. In this study, composite ferrate solution (CFS) has been used to disintegrate WAS. The results showed that CFS could effectively disrupt sludge flocs and cells and caused the release of intracellular matter such as SCOD, cations and organic acids. These results showed that the sludge disintegration process could be divided into a rapid reaction stage (0–2 h) and a slow reaction stage (2–24 h). It was determined that at a CFS dosage of 50 mg Fe/g SS and a reaction time of 24 h, the sludge reduction was 55.4% and SV and SVI were reduced by 12.1% and 46.4%, respectively. The Fe(VI), ClO − and OH − in CFS all played important roles in sludge decomposition, but they did not have synergistic effects. The small-particle sludge, in situ formed Fe 3+ and released Ca 2+ could improve the sludge settleability.